Consonant Confusion: Pronunciation Challenges among English Club Members - Dewi, Ni Komang Nira; Hikmaharyanti, Putu desi Anggerina (Linguistics and ELT Journal, 2025)
This study examines pronunciation errors among university students learning English as a second language, focusing on members of the English Club, primarily Balinese learners. Despite English being a global language and widely learned as a second language, pronunciation remains a significant challenge, often influenced by the learners' native language. This research employs a qualitative approach with purposive sampling to select a sample of 11 participants who are not majoring in English. These participants were chosen through observation and a questionnaire. Data are collected by having the participants read a story, "Pan Balang Tamak," to identify specific pronunciation errors and understand how their native language affects their English pronunciation. This research finds that the most type of error is misformation in some sounds such as /θ/, /ð/, /ʃ/, /tʃ/, /dʒ/, /ʒ/. This type of error occurs due to the dissimilarity of certain sounds between English and the native language. Additionally, pronunciation skills among English Club members must be improved to reduce recurring errors